The LFDD - human mobility nexus in Africa, Latin America and the Caribbean: A review of national policy and legal frameworks - Diogo Andreola Serraglio (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Although extreme weather events and slow onset processes have been increasingly linked to human mobility in distinct international governance spaces, research and policy on migration, displacement and planned relocation resulting from slow onset events remain focused mainly on sea level rise or specific hazards such as prolonged droughts. Land and forest degradation and desertification (LFDD), as a driver of population movements and its implications for long-term development policy, have received less attention. Considering the far-reaching impacts of these processes on human systems, this discussion paper aims to examine to what extent the LFDD - human mobility nexus has been integrated in existing policy and legal frameworks in African, Latin American and Caribbean (LAC) countries, identifying pathways towards improved management of population movements related to slow onset events. In this context, this discussion paper also presents national responses to the current COVID-19 pandemic, which has increased vulnerability in areas affected by progressive environmental changes. The analysis builds upon a review of policy and legal documents, and it sets the groundwork for an advanced research and policy agenda on human mobility in the context of LFDD. Even though efforts have been made to acknowledge the topic in African and LAC nations, the findings suggest the need for wider consideration of the LFDD - human mobility nexus in existing domestic frameworks.
Keywords: 330